A Theoretical Model for Urban Walking Among People With Disabilities - Marcheschi, Elizabeth; Ståhl, Agneta; Almén, Mai; Johansson, Maria (Frontiers in Psychology, 2020)
This paper is an attempt to advances research on walking, at a neighbourhood level of analysis for people with disabilities, by proposing a theoretical model that combines the knowledge of two disciplines: traffic planning and environmental psychology. The aim is to provide a guidance for a discussion and a planning of future interdisciplinary investigations, by proposing a model that accounts for the dynamic interaction between environmental characteristics, human processes, and walking experience among individuals with a disability. For this purpose, traffic planners and environmental psychologists came together to discuss theories, concepts, and thematic of relevance in a series of focus group meetings. These meetings led to the selection of the Human Environment Interaction (HEI) model, originally developed from the field of environmental psychology, and operationalised to describe how walking experiences result from the interplay between individual abilities, emotional processes and physical and social characteristics of the environment (Küller, 1991). The proposed model aims to sustain interdisciplinary discussion and research planning around the topic of neighbourhood walking for people with disabilities. By operationalising each dimension in the model, a good fit between groups with disabilities and individual differences associated with walking experiences is assumed, which in turn will have the potential to provide a more conscious analysis of wellbeing-related outcomes such as, usability of the environment, frequency of mobility, and quality of life. However, to improve understanding of urban walking at a neighbourhood level for people with disabilities, empirical studies must be carried out to test the proposed model.